Integrating Hyperthermia into Modern Radiation Oncology: What Evidence Is Necessary? - Peeken, Jan C.; Vaupel, Peter; Combs, Stephanie E. (Frontiers in Oncology, 2017)
Hyperthermia is one of the hot topics that have been discussed over decades. However, it never made its way into primetime. The basic biological rationale of heat to enhance the effect of radiation, chemotherapeutic agents and immunotherapy is evident. Preclinical work has confirmed this effect. Hyperthermia may trigger changes in perfusion and oxygenation as well as inhibition of DNA repair mechanisms. Moreover, there is evidence for immune stimulation and the induction of systemic immune responses. Despite the increasing number of solid clinical studies only few centers have included this adjuvant treatment into their repertoire. Over the years, abundant prospective and randomized clinical data have emerged demonstrating a clear benefit of combined hyperthermia and radiotherapy for multiple entities such as superficial breast cancer recurrences, cervix carcinoma or cancers of the head and neck. Regarding less investigated indications, the existing data is promising and more clinical trials are currently recruiting patients. How do we proceed from here? Preclinical evidence is present. Multiple indications benefit from additional hyperthermia in the clinical setting. This article summarizes the present evidence, and develops ideas for future research.